Board of directors and credit risk: An empirical study of Indonesian Islamic banks - Peni Nugraheni; Rifqi Muhammad (University of Merdeka Malang, 2019)
Credit risk is the primary risk in the banking industry related to its function in distributing credit to customers. Decreasing credit risk is the main duty of the management of banks. We examine the relationship between the Board of Directors (BOD) characteristics and credit risk in the Indonesian Islamic bank. BOD characteristics consist of BOD size, educational qualification, number of meetings, and expertise. The samples in this study are full-fledged Islamic banks in Indonesia that publish annual reports for the year 2013-2017. The data are processed using panel data regression. We indicate that the number of BOD meetings has a negative influence on credit risk, BOD size has a positive influence on credit risk while educational qualification and expertise do not influence credit risk of Islamic banks in Indonesia. Understanding BOD characteristics and credit risk are useful to mitigate the implementation of corporate governance for Islamic banks in the two-tier board system. The findings are expected to have a contribution to strengthening the BOD’s role to encourage the better performance of Islamic banks.JEL Classification: G21, G32DOI: https://doi.org/10.26905/jkdp.v23i4.3484